Pengaruh Kapasitas Panel Surya dan Intensitas Cahaya Matahari terhadap Kinerja Generator Hidrogen Kering dalam Produksi Gas Hidrogen - Rezha Apriansyah; Rifky; Tasyrik Al Qaida; Dicky Wyldan Putra Permana; Saddam Firly Mustarisiam (Prosiding Seminar Nasional Teknoka, 2025)
Hydrogen gas can be obtained from a hydrogen generator generated by solar panels. This study aims to obtain the performance of an integrated solar panel system with a dry hydrogen generator (GHK) in producing hydrogen gas. GHK has a design with an arrangement of HSS 316L type steel plates coated with rubber gaskets. The research methodology used is experimental, starting with the design of the GHK electrolysis system using two solar panels with a capacity of 50 Wp and 100 Wp as electrical energy suppliers. The test was carried out in an open area using sunlight. The input data measured included sunlight intensity, air humidity, air temperature, wind speed, and solar panel surface temperature. The output data measured included electrical voltage, electrical current, hydrogen gas discharge, oxygen gas discharge, electrolysis process temperature, and weather conditions. The results showed that the system with a 100 Wp solar panel produced a larger volume of hydrogen and had a higher efficiency of energy conversion than the 50 Wp panel.